Partial Sums for Normalized Mittag-Leffler-Prabhakar Function and Barnes-Mittag-Leffler Function (European Journal of Pure and Applied Mathematics, 2025)
Building on recent research that established partial sum and lower bounds for various special functions, this paper extends the scope to investigate the normalized Le Roy-type Mittag-Leffler-Prabhakar and Barnes-Mittag-Leffler functions. We aim to determine lower bounds for these functions and their partial sums. We  also presenting some new consequences, lemmas, and corollaries that highlight the significance of our findings. Our results are novel and enhance existing knowledge in the field.
Keywords: Univalent functions; Partial sums and Lower bounds; Mittag-Leffler and Barnes-Mittag-Leffler functions.; Le Roy-type Mittag-Leffler function